Nature - Kastner, Jeffrey; Kastner, Jeffrey; Haraway, Donna; Reichle, Ingeborg; Latour, Bruno; Agamben, Giorgio; Auping, Michael; Bachelard, Gaston; Whitechapel Art Gallery (London : Whitechapel Gallery, 2012)
Aziz & Cucher ; Ballengée, Brandon ; Berwick, Rachel ; Beuys, Joseph ; Catts, Oro ; Chin, Mel ; Coates, Marcus ; Cooper, Justine ; Critical Art Ensemble ; De Maria, Walter ; Denes, Agnes ; Dion, Mark ; Fulton, Hamish ; Haacke, Hans ; Hakansson, Henrik ; Harrison Helen ; Harrison, Newton ; Huyge, Pierre ; Jeremijenko, Natalie ; Kac, Eduardo ; Mattingly, Mary ; Mendieta, Ana ; Mignonneau, Laurent ; Morris, Robert ; Prophet, Jane ; Renhui, Zhao ; Rockman, Alexis ; Sherk, Bonnie ; Smithson, Robert ; Sommerer, Christa ; Sonfist, Alan ; Stelarc ; Tiravenija, Rirkrit ; Ukeles, Mierle Laderman ; Vesna, Victoria ; Zittel, Andrea
Formerly CIP.
boek
Keywords: Nature in art; Arts, Modern -- Themes, motives